Economic Consequences of Lower Military Spending : Some Simulation Results - Schiff, Jerald (IMF Working Papers; Working Paper ;, 1993)
The IMF MULTIMOD model is used to trace the economic impact of a 20 percent reduction in world military expenditures. GDP falls in the short run, however private consumption and investment rise, leading to an increase in GDP in the medium and long run. The estimated gains to economic welfare are substantial, particularly for developing countries, although most of these gains are realized in the long run. A positive international economic externality is found to exist, implying that for any given country the economic gains from a coordinated reduction in military expenditures exceed the gains from a unilateral reduction.